Bimetallic MOF‐Derived FeCo‐P/C Nanocomposites as Efficient Catalysts for Oxygen Evolution Reaction. Issue 12 (23rd August 2018) - Hong, Wei; Kitta, Mitsunori; Xu, Qiang
Abstract: Oxygen evolution reaction (OER) demands cost‐effective electrocatalysts with high catalytic performance. In this effort, metal–organic framework (MOF)‐derived nanocomposites are presenting promising prospects to achieve this goal. Herein, FeCo bimetallic MOFs with different compositions are prepared through a sodium hydroxide assisted approach. By means of a successive carbonization and phosphating reaction, a series of MOF‐derived multicomponent products are synthesized. The resultant P‐doped products present enhance electrocatalytic performance for OER in alkaline electrolyte in comparison with a commercial RuO2 catalyst, which paves the way for their practical applications for water splitting. The developed method herein also offers an opportunity for the large‐scale preparation of MOF‐derived product toward energy conversion applications. Abstract : An efficient water‐phase sodium hydroxide‐mediated method to prepare bimetallic FeCo metal–organic framework (MOF) with high yield is developed. Through a carbonization and P‐doping process of these MOFs, metallic nanoparticles/carbon nanocomposites with multicomponents are prepared. The resultant P‐doped products achieve better oxygen evolution reaction performance compared with the monometallic Co MOF‐derived product and a commercial RuO2 catalyst.